2006
DOI: 10.1242/jcs.03012
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the PI 3-kinase–Akt signalling pathway by IGF-I and PTEN regulates the differentiation of neural stem/precursor cells

Abstract: Neural stem cells depend on insulin-like growth factor I (IGF-I) for differentiation. We analysed how activation and inhibition of the PI 3-kinase–Akt signalling affects the number and differentiation of mouse olfactory bulb stem cells (OBSCs). Stimulation of the pathway with insulin and/or IGF-I, led to an increase in Akt phosphorylated on residues Ser473 and Thr308 (P-AktSer473 and P-AktThr308, respectively) in proliferating OBSCs, and in differentiating cells. Conversely, P-AktSer473 levels decreased by 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 53 publications
11
111
1
2
Order By: Relevance
“…Many reports have suggested that PTEN plays a critical role in brain development and cell phenotype changes [7,14,15]. In order to further investigate the role of PTEN in cAMP-regulated cell growth, we performed western blotting analyses using the phospho-specific antibodies, phospho-PTEN (Ser380) antibody and phospho-Akt (Ser473) antibody.…”
Section: Camp-stimulating Agents Promote Morphological Changesmentioning
confidence: 99%
“…Many reports have suggested that PTEN plays a critical role in brain development and cell phenotype changes [7,14,15]. In order to further investigate the role of PTEN in cAMP-regulated cell growth, we performed western blotting analyses using the phospho-specific antibodies, phospho-PTEN (Ser380) antibody and phospho-Akt (Ser473) antibody.…”
Section: Camp-stimulating Agents Promote Morphological Changesmentioning
confidence: 99%
“…Namely, changing the state of microglial activation from highly-activated to proliferating was associated with the signiWcant decrease in TNF-production and the increase in IGF-1 secretion [79]. IGF-1 is a known anti-apoptotic factor and recent reports suggest that it plays an important role in promotion of proliferation and diVerentiation of neuronal progenitors [65,107,145]. Contrary to IGF-1, the studies performed on the transgenic animals lacking TNFR1 revealed that TNFR1 acts as a negative regulator of neuronal progenitors in hippocampus and in SVZ area after stroke [59,60].…”
Section: How Brain Inxammatory Response To Ischemic Injury May Avect mentioning
confidence: 99%
“…A majority of growth factors bind to their receptors and activate downstream signaling pathways to induce the expression of specific genes responsible for proliferation, differentiation, and/or migration of cells. For example, receptor-mediated activation of mitogen-activated protein kinase promotes the proliferation, 33 whereas stimulation of the phosphoinositide-dependent kinase/Akt pathway enhances the differentiation 30 of the neural stem cells. Nevertheless, some growth factors like TGF␤ and BMP-4 13 can promote the differentiation of neural stem cells by activating proteins (such as Smads), which are translocated into the nucleus to induce gene expression.…”
Section: Role Of Growth Factorsmentioning
confidence: 99%